Dynamika liczebności, skład pokarmu i produktywność populacji krogulca Accipiter nisus L. w warunkach środkowej Polski - Gryz, Jakub; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2018)
Long-term monitoring of raptor populations can serve as a proxy for the evaluation of whole ecosystem health. The aim of the study was to compare the current abundance of the sparrowhawk Accipiter nisus L. with data from past decades. Additionally, we examined the diet of this species in the breeding season and recorded the number of fledglings. The study area encompassed 105 km 2 of field and forest mosaic, located in the vicinity of the Rogów village (51°49’17,98”N, 19°53’54,5”E). Forests covered approximately 24% of the area and formed eight individual complexes ranging in size from 65 ha to 1000 ha. In the years 2011–2017, an average of 20.1 sparrowhawk pairs were recorded resulting in a population density of 19.1 pairs per 100 km 2 of total area and 8.2/10 km 2 of forested area. This is an increase of 26% compared to the years 2001–2003, when only 16 pairs nested in the same study area. Each successful pair of sparrowhawk produced between one and five fledglings with the average being 3.4. Larch Larix spp. and Scots pine Pinus sylvestris L. dominated as nesting trees accounting for 36.9 and 35.9% of nesting sites respectively. The average age of the nesting trees was 31 years and nests were built at an average height of 11.7 m. The sparrowhawk diet was dominated by birds, which amounted to 81.5% of prey items and over 95% of the consumed biomass. Among the birds identified to the species level, the domestic pigeon Columba livia f. domestica Gm. constituted the biggest share in biomass. Further important prey items were starling Sturnus vulgaris L., with 5.6% of prey items and 9.8% of the total biomass, and hawfinch Coccothraustes coccothraustes (L.), with 6.3% of prey items and 7.6% of the total biomass. Sparrowhawks also consumed significant numbers of thrush Turdus spp. that formed in total over 11% of the total consumed biomass. It would appear that the observed population growth was a result of prohibited persecution and the ban on DDT usage in agriculture.